The dynamic changes of soil air‐filled porosity associated with soil shrinkage in a Vertisol. (26th October 2022) - Wang, Yuekai; Zhang, Zhongbin; Guo, Zichun; Xiong, Peng; Peng, Xinhua
Abstract: Soil aeration is critical for crop growth, which is generally assessed by air‐filled porosity (AFP). In non‐rigid soils with high shrinkage and swelling, the AFP is not only related to the total porosity and soil moisture, but also to the soil shrinkage behaviour. However, the relationship between AFP and soil shrinkage has not been clarified. The objectives of this study were to (1) establish a mathematical equation to describe the behaviours of AFP associated with soil shrinkage (AFPsh ); and (2) to evaluate the influence of tillage practice on the AFPsh . Undisturbed soil core samples were collected from the 0–10 cm to 10–20 cm layers in a Vertisol under four tillage treatments (No tillage, NT; Rotary tillage, RT; Subsoiling, SS; Deep ploughing, DP) to measure the changes in the volumes of soil core, soil water and air at different soil matric potentials. Our results showed that an equation of AFPsh as a function of moisture ratio ( ϑ ) was well established based on the developed soil shrinkage model ( R 2 > 0.990, RMSE <0.012). Compared with the AFP under a constant pore assumption (AFPc ), the AFPsh was significantly decreased by 10.6% to 60.3% as soil water matric potentials were at <−33 kPa in the 0–10 cm layer or at <−10 kPa in the 10–20 cm layer ( p < 0.05). According to the AFPsh curve of the Vertisol, soil moisture content ( θ ) was approximately 68%–80% of the field capacity when AFPsh reached non‐limiting status (0.10 cm 3 cm −3 ), where the soil matric potential was close to the wilting point (−1500 kPa). Deep tillage treatment (SS and DP) increased AFPsh, showing good performance in decreasing the risk of soil aeration deficit relative to the NT and RT treatment. Our results demonstrate that neglecting the porosity variations during shrinkage may lead to a high bias in the AFP prediction. Highlights: An equation of AFP associated with soil shrinkage was established. AFP was significantly decreased when soil shrinkage was considered for a Vertisol. The Vertisol was easily subjected to both water and air stress due to soil shrinkage. Deep tillage practises improved soil aeration in the Vertisol.